2023
DOI: 10.1002/cbic.202300291
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobase and Linker Modification for Triple‐Helical Recognition of Pyrimidines in RNA Using Peptide Nucleic Acids

Abstract: Triple-helical recognition of any sequence of double-stranded RNA requires high affinity Hoogsteen hydrogen binding to pyrimidine interruptions of polypurine tracts. Because pyrimidines have only one hydrogen bond donor/acceptor on Hoogsteen face, their triple-helical recognition is a formidable problem. The present study explored various five-membered heterocycles and linkers that connect nucleobases to backbone of peptide nucleic acid (PNA) to optimize formation of X * C-G and Y * U-A triplets. Molecular mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…While the K a for PNA6-HRP5 and PNA7-HRP6 was 1 and 3 × 10 6 M −1 , respectively, stability of PNA8-HRP7 and PNA9-HRP8 was too low to be measured by ITC or UV melting under our usual conditions. 51 Taken together, these results show that recognition of pyrimidines using simple heterocycles forming one hydrogen bond is a challenge and remains an unsolved problem for triplex-forming PNAs.…”
Section: Sequence Scope Of Triple Helical Recognitionmentioning
confidence: 76%
See 3 more Smart Citations
“…While the K a for PNA6-HRP5 and PNA7-HRP6 was 1 and 3 × 10 6 M −1 , respectively, stability of PNA8-HRP7 and PNA9-HRP8 was too low to be measured by ITC or UV melting under our usual conditions. 51 Taken together, these results show that recognition of pyrimidines using simple heterocycles forming one hydrogen bond is a challenge and remains an unsolved problem for triplex-forming PNAs.…”
Section: Sequence Scope Of Triple Helical Recognitionmentioning
confidence: 76%
“…The extended linker that connected E to PNA backbone was expected to circumvent steric hindrance from the 5-Me of T and allow E to form a single hydrogen bond with the C4 carbonyl of T. 50 We found that E also recognized U-A base pairs in RNA with good affinity (Fig. 4, K a = 11 × 10 6 M −1 and T m = 54 °C) albeit the sequence specificity was lower than for M and T. 46,51 Molecular modeling suggested that in PNA-dsRNA triplexes E formed one hydrogen bond with U (Fig. 3) as originally proposed for the E•T-A triplet in DNA.…”
Section: Sequence Scope Of Triple Helical Recognitionmentioning
confidence: 92%
See 2 more Smart Citations